Design of Immune-Algorithm-Based Adaptive Fuzzy Controllers for Active Suspension Systems. (28th April 2014) - Shieh, Ming-Yuan; Chiou, Juing-Shian; Liu, Ming-Tang
Abstract : The aim of this paper is to integrate the artificial immune systems and adaptive fuzzy control for the automobile suspension system, which is regarded as a multiobjective optimization problem. Moreover, the fuzzy control rules and membership controls are then introduced for identification and memorization. It leads fast convergence in the search process. Afterwards, by using the diversity of the antibody group, trapping into local optimum can be avoided, and the system possesses a global search capacity and a faster local search for finding a global optimal solution. Experimental results show that the artificial immune system with the recognition and memory functions allows the system to rapidly converge and search for the global optimal approximate solutions.